EVALUATION OF PRO-C GLOBAL FOR IDENTIFICATION OF DEFECTS IN PROTEIN C/S ANTICOAGULANT PATHWAY - Hanif, Tamoor Bin; Anwar, Jaleel; Idrees, Muhammad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Detection of protein C and S deficiency forms a major investigation in the laboratory evaluation of thrombophilia screening. It has key role in the diagnosis of protein C and S deficiency. The objective of this study is to determine the utility of ProC Global as a screening test for identifying the defects of protein C and S anticoagulant pathways. Methods: Two Hundred patients with venous thromboembolism were studied at the Department of Haematology, Armed Forces Institute of Pathology, Rawalpindi, from October 2004 to March 2006. ProC Global test (Dade Behring Diagnostics) was performed and was followed up by protein C and S assays. ProC Global is an activated partial thromboplastin time based assay in which Protac (snake venom from Aghistroden contortrix) is used for activation of the endogenous protein C of the plasma sample. The protein C activation time in the presence of the activator was set in relation to a parallel determination of PCAT/O with addition of a buffer instead of activator reagent. The ratio PCAT: PCAT/O was transformed in normalized ratio by relating them to a calibrator. Control plasma for normal range and ProC control plasma for pathological range (Dade Behring Diagnostics) were assayed in each run for quality control. Results: A total of 200 patients, 132 (66%) males and 68 (34%) females with age ranging from 1 to 68 years were studied. ProC Global was positive in 29/200 (14.5%) patients. ProC Global was found to be 86% sensitive, 94% specific and its overall efficiency turned out to be 94%. Conclusion: Pro-C Global can be used effectively as a screening test to detect abnormalities in protein C and S anticoagulant pathways. Keywords: Protein C deficiency, Protein S deficiency, Thrombophilia